Small and medium-sized enterprise finance in Uzbekistan: Challenges and opportunities - Dildora Tadjibaeva (Asian Development Bank Institute (ADBI), 2019)
Uzbekistan set an ambitious goal to achieve the status of an upper-middle-income country by 2030, with the focus on growing a large and solid middle-class social stratum. The current reforms in Uzbekistan largely target the development of small businesses and private entrepreneurship (SME) as SMEs have the greatest potential for becoming a real basis for forming a middle class. This paper provides an overview of small business development in Uzbekistan, highlighting the evidence of social economic importance of the SME, and discusses the current status and perspectives of SME policy. The paper also describes the availability of and gaps in SME financing, discusses the key issues of SME finance and current financial literacy programs available in the country, including SME literacy program delivery. Among others, the paper explores the special focus on SME participation in the global value chain and accessibility of value chain financing. The study results in a set of recommendations aimed to improve access to finance among SMEs and facilitate the development of a more competitive market economy in Uzbekistan.
Keywords: G2; G3; G21; G28; O16; 330; financial inclusion; financial literacy and education; SME; value chain